2020
DOI: 10.3390/v12040459
|View full text |Cite
|
Sign up to set email alerts
|

The Nef Protein of the Macrophage Tropic HIV-1 Strain AD8 Counteracts Human BST-2/Tetherin

Abstract: Bone Marrow Stromal Cell Antigen 2 (BST-2)/tetherin inhibits the release of numerous enveloped viruses by physically tethering nascent particles to infected cells during the process of viral budding from the cell surface. Tetherin also restricts human immunodeficiency virus (HIV), and pandemic main (M) group HIV type 1s (HIV-1s) are thought to rely exclusively on their Vpu proteins to overcome tetherin-mediated restriction of virus release. However, at least one M group HIV-1 strain, the macrophage-tropic prim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Thus, with respect to BST-2 modulation, Vpu performs parallel roles on CD4 + T cells and macrophages. Of note, we observed that for HIV-1 AD8 and YU2, full recovery of BST-2 levels at the cell surface required Nef deletion (N-U-), in agreement with a recent report suggesting that Nef from some HIV-1 strains, including AD8 can downregulate BST-2 (Giese et al, 2020).…”
Section: Hiv-1 Mediated Cd4 Downregulation In Macrophagessupporting
confidence: 92%
“…Thus, with respect to BST-2 modulation, Vpu performs parallel roles on CD4 + T cells and macrophages. Of note, we observed that for HIV-1 AD8 and YU2, full recovery of BST-2 levels at the cell surface required Nef deletion (N-U-), in agreement with a recent report suggesting that Nef from some HIV-1 strains, including AD8 can downregulate BST-2 (Giese et al, 2020).…”
Section: Hiv-1 Mediated Cd4 Downregulation In Macrophagessupporting
confidence: 92%
“…Of note, we observed that for HIV-1 AD8 and YU2, full recovery of BST-2 levels at the cell surface required Nef deletion (N–U–), in agreement with a recent report suggesting that Nef from some HIV-1 strains, including AD8, can downregulate BST-2. 38 …”
Section: Resultsmentioning
confidence: 99%
“…A direct BST2-Nef interaction separates BST2 from virus-release sites at the plasma membrane through endocytosis and promotes BST2 lysosomal degradation ( Serra-Moreno et al., 2013 ). The M group HIV-1 strain AD8, unable to express Vpu owing to a mutation, utilizes Nef to enhance BST2 internalization and perinuclear accumulation without BST2 degradation ( Giese et al., 2020 ). Although the specific mechanism is not fully known, the available results show that neither Env nor Nef can decrease BST2 through the ubiquitin-proteasome system, suggesting that BST2 presents a barrier to initial HIV transmission to humans.…”
Section: Hiv-1 Antagonistic Action and Mechanism Against Bst2mentioning
confidence: 99%